Acute-onset stomatitis in a young European woman visiting Brazil: a case report - Aleksandra Kierczak; Tomasz Smiatacz; Marta Katkowska; Katarzyna Garbacz (Frontiers in Oral Health, 2025)
We report a case of acute, severe stomatitis in a 20-year-old European woman shortly after her arrival in Brazil following participation in a multi-day carnival. The clinical picture was consistent with either primary herpes simplex virus type 1 (HSV-1) infection or herpangina caused by enteroviruses. Due to the absence of virological testing, a definitive diagnosis was not established. Empirical treatment with corticosteroids and antibiotics was initiated, while antiviral therapy was omitted. The patient's symptoms progressed significantly before resolving with supportive care within ten days. This case underscores the diagnostic challenges of viral oral infections in adults, especially in travelers exposed to novel pathogens. It highlights the importance of bedside diagnostic tools, the potential risks associated with empirical corticosteroid use, and the need to enhance clinician awareness of viral stomatitis as a significant and potentially debilitating condition in adult patients.